TEORI BELAJAR HUMANISTIK DAN IMPLEMENTASINYA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Ariansyah, Mochamad Yunus; Anam, Insan Syariful; Zaman, Badrus (STAINU Purworejo, 2023)
So far the educational process that has taken place in Indonesia has not implemented a humanistic learning process which plays an important role in this case because it will form students who have a sense of humanizing humans.Therefore, researchers try to choose topics for discussion of humanistic theory with the aim that the learning process in formal institutions such as schools can better understand what talents or potential students have so that they do not directly justify these students. The method used in writing this article is qualitative by using a literature study method. This research, is descriptive, trying to see the existing theory, then trying to illustrate it, then implementing it into the learning process of Islamic religious education. The conclusion obtained is that in humanistic learning theory, a teacher or mentor serves as a facilitator, meaning that the teacher assists with a humanist approach that students feel interested in and enthusiastic about. Also, the facilitator here must be flexible to students in delivering material by using strategies that promote active, creative, and fun learning so that students can actualize material that can be incorporated into their daily lives. Therefore, one of the implementations of humanistic theory in PAI learning is the peer-tutoring technique, in which students considered to have understood and are qualified in one material are ask